Post-translational Modifications of Fumarase Regulate its Enzyme Activity and Function in Respiration and the DNA Damage Response. Issue 23 (20th November 2020) - Wang, Suqing; Ramamurthy, Dharanidharan; Tan, Jasper; Liu, Jingyan; Yip, Joyce; Chua, Andrea; Yu, Zhang; Lim, Teck Kwang; Lin, Qingsong; Pines, Ophry; Lehming, Norbert
Graphical abstract: Highlights: The tumor suppressor class-II fumarase functions in the DNA damage response in yeast. The specific enzymatic activity of fumarase increases upon DNA damage. Fumarase is found to be phosphorylated, succinylated, ubiquinated and deamidated. Removal of modifications at six residues upon DNA damage activates fumarase. Recruitment to the site of damage is not a requirement for fumarase to aid DNA repair. Abstract: The Krebs cycle enzyme fumarase is a dual-targeted protein that is located in the mitochondria and cytoplasm of eukaryotic cells. Besides being involved in the TCA cycle and primary metabolism, fumarase is a tumour suppressor that aids DNA repair in human cells. Using mass spectrometry, we identified modifications in peptides of cytosolic yeast fumarase, some of which were absent when the cells were exposed to DNA damage (using the homing endonuclease system or hydroxyurea). We show that DNA damage increased the enzymatic activity of fumarase, which we hypothesized to be affected by post-translational modifications. Succinylation and ubiquitination of fumarase at lysines 78 and 79, phosphorylation at threonine 122, serine 124 and threonine 126 as well as deamidation at arginine 239 were found to be functionally relevant. Upon homology analysis, these residues were also found to be evolutionally conserved. Serine 128, on the other hand, is not evolutionary conserved and the Fum1S128D phosphorylation mimic was able to aid DNA repair. Our molecular model is that the above modifications inhibit the enzymatic activity of cytosolic fumarase under conditions of no DNA damage induction and when there is less need for the enzyme. Upon genotoxic stress, some fumarase modifications are removed and some enzymes are degraded while unmodified proteins are synthesized. This report is the first to demonstrate how post-translational modifications influence the catalytic and DNA repair functions of fumarase in the cell.